Clinical relevance of amnestic versus non‐amnestic mild cognitive impairment subtyping in Parkinson's disease. (20th January 2019) - Chung, S. J.; Park, Y.‐H.; Yun, H. J.; Kwon, H.; Yoo, H. S.; Sohn, Y. H.; Lee, J.‐M.; Lee, P. H.
Abstract : Background and purpose: To clarify whether subtyping of amnestic and non‐amnestic mild cognitive impairment (MCI) is clinically relevant in Parkinson's disease (PD) by analyzing patterns of neuroimaging and longitudinal cognitive changes. Methods: We performed comparative analyses of cortical thickness, hippocampal volume, white matter integrity and resting‐state functional connectivity between the patients with de‐novo PD with amnestic MCI (PD‐aMCI) ( n = 50) and non‐amnestic MCI (PD‐naMCI) ( n = 50) subtypes. Additionally, we assessed the longitudinal rate of cognitive decline in each cognitive domain over time and the rate of dementia conversion in patients with de‐novo PD‐aMCI ( n = 125) and PD‐naMCI ( n = 61). Results: The demographic data showed that scores in memory domains were lower in the PD‐aMCI group compared with the PD‐naMCI group. There were no significant differences in cortical thickness, hippocampal volume and white matter integrity between the two groups, although the PD‐aMCI group exhibited more cortical thinning and hippocampal atrophy relative to the control group. The PD‐aMCI group exhibited increased functional connectivity in the left posterior parietal region with the salience network relative to the PD‐naMCI group. The longitudinal cognitive assessment demonstrated that patients with PD‐aMCI exhibited a more rapid cognitive decline in frontal/executive function than those with PD‐naMCI ( P = 0.022). In addition, the PD‐aMCI group had a higher risk of dementia conversion than the PD‐naMCI group. Conclusions: This study suggests that the designation of PD‐MCI subtypes based on memory function would highlight the heterogeneity of functional correlates as well as the longitudinal cognitive prognosis.